Optimasi Liposom Sebagai Sistem Penghantaran Obat - Sri Mulyanthy Tanuwidjaja; Dhea Quraeny Herawan; Dedeh Indah; Indriani Sukmawati; Safitri Safitri; Sri Ayu Winarti; Windi Ikhtianingsih; Nia Yuniarsih (Syntax Literate, 2022)
Pharmaceutical formulation technology and drug delivery systems play an important role in the process of discovering new pharmaceutical therapies to the public. Physicochemical and molecular considerations including ion-molecular equilibrium, hydrophilic-lipophilic equilibrium, biopharmaceutical processes, metabolism and biodegradation, drug-receptor affinity, physiological considerations, and biocompatibility of the system are the main factors (Ronny Martien et al, 2012). Liposomes are pharmaceutical preparations developed in the pharmaceutical world because liposomes have advantages, including increasing the efficacy and therapeutic index and increasing drug stability with encapsulation systems (Akbarzadeh et al, 2013). Liposomes are usually formed from a phospholipid, which is commonly used to change the pharmacokinetic profile of a drug, natural compound, vitamin or enzyme. Liposomes have been widely studied for natural compounds. Due to their unique properties, liposomes can be used to improve the performance of herbal products by increasing solubility, improving BA, increasing intracellular uptake, changing pharmacokinetic profiles and biodistribution (Aulia, 2022). The purpose of this study was to determine the optimization of liposomes as a drug delivery system. This study uses the Literature Review method. The results showed that liposomes could improve the therapeutic activity and safety of the drug, particularly by delivering the drug at the site of action and regulating drug levels at therapeutic concentrations over an extended period of time. (Sriwidodo, 2022).